Comparison of clinical and CSF profiles in 62 Adults with tuberculous and pyogenic meningitis - Kumar, Munish; Kumar, Durgesh; Sahu, Alok Onkar; Rastogi, Manoj Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Many a times differentiating tuberculous meningitis from pyogenic meningitis becomes very difficult. The diagnosis depends upon clinical manifestation and cytochemical analysis of cerebrospinal fluid (CSF). Many researchers found that the CSF glucose: protein ratio less than 0.5 and Adenosine deaminase levels (ADA) in cerebrospinal fluid are useful to differentiate tubercular disease from non-tubercular meningitis. Methods: Sixty-two patients admitted to our tertiary hospital with symptoms and signs of meningitis were selected and divided into two groups: tubercular (n=39) and pyogenic (n= 23), depending upon the accepted criteria. Clinical features and CSF parameters noted in each patient. Cut off value of ADA kept at or above 10 IU/L for tubercular meningitis. Results: The mean age of patients with tubercular meningitis was 39.07±16.67 years and that of pyogenic meningitis 34.35±16.73 years. Clinically fever was present in 60 (96.77%), headache in 49 (79.03%), and vomiting in 44 (70.96%) patients. Meningeal signs – neck rigidity in 46 (74.2%), Kernig’s sign in 37 (59.68%) and Brudzinski’s sign in 18 (29.03%) patients. On CSF cytological and biochemical analysis the mean total white blood cell count was 256.74±184.03 /cmm, mean protein 182.22±113.12 mg/dl and mean sugar 52.85±19.3mg/dl in TBM whereas in pyogenic meningitis 106.17±185.18 / cmm, 88.78±114.35 mg/ dl, and 63.47±19.48 mg/dl respectively. Out of 39 tuberculous patients, 33 patients were found to be having CSF ADA at or above the cutoff value of 10 IU/L while only one among pyogenic meningitis. On comparison between two groups, the CSF ADA level found to be statistically highly significant (P < 0.001) with overall accuracy of the test was 85.5 %. Conclusions: We found that the duration of illness, estimation of cerebrospinal fluid ADA with a cut off value of 10 IU/L and CSF glucose: protein ratio of 0.5 may useful in differentiating tuberculous from pyogenic meningitis. posterior cranial fossa surgeries. This work will also be useful to anthropologists, forensic science experts for determination of sex of the skull along with other parameters.